Filsafat Hukum Sejarah: Konsep dan Aktualisasinya Dalam Hukum Indonesia - Indra Rahmatullah (ADALAH, 2021)
Abstract: Society has  own legal system, namely customary law which can be a source of national law. It exists and has been legitimized in the Indonesian constitution. With the recognition of customary law, law enforcers and lawmakers must consider it. Customary law is not made by the State, but exists, and develops with the development of society. In certain areas, the application of customary law or compliance with customary law is more binding than state law. The basic concept of customary law is from the thought of Friedrick Karl von Savigny through his various works, thus making him the philosopher who built the foundation for the School of Legal History. Keywords: Society; Customary Law; Legal History